Factors influence minimum wage in selected OECD countries / Nur Sakinah Sarnoh - Sarnoh, Nur Sakinah (2020)
This research main focus is to study the determinants of the minimum wages in selected Organization for Economic Co-operation and Development (OECD) countries. The researcher want to analyze what factors that able to contributing on minimum wage rates. The value for minimum wage has been decreased and increased since it was introduces during 1930s. Using total three of independent variables, which is economic growth, inflation and population, this study involving data for selected eighteen countries member of OECD for 26 years which is from the 1993 until 2018. This study using panel-data analysis for data regression and by the end of the study finding, only economic growth that has significant relationship with the minimum wage.